The Governor, the Cow-Head, and the Thrashing Pillows: Negotiated "Restrictive Islam" in Early Twenty-First Century Southeast Asia? - Satha-Anand, Chaiwat (Religions, 2022)
There are obviously several ways to explore the issue of Islamic radicalism in Southeast Asia. Instead of focusing on explicit violence such as those carried out by jihadi groups or those associated with them, this research article chooses to examine three empirical cases of Muslims’ expression of "restrictive Islam" that have taken place in the public sphere in both majority and minority Muslim contexts of Southeast Asia. They are: Muslims’ calling for the removal of an elected Chinese Christian governor of Jakarta on account of blasphemy in Indonesia; Muslims’ cow head protest to intimidate Hindus in Malaysia; and some Muslims’ thrashing of pillows at a hospital for COVID-19 patients as an expression of vehement faith-based refusal and protest in Buddhist Thailand against health protocols issued by Thai officials in the current fight against the pandemic in Southern Thailand. This article argues that the "restrictive" lives that some Muslims lead in Southeast Asia today have to assume a negotiated form that is a mixture of "high artificiality", recently adopted from a version of purist Islam they claim to be authentic, and the "pure normality" resulting from a combination of political reality informed by existing forms of governance in these countries and the legacy of how historical Islam arrived in this land. The result is that the "restrictive Islam" espoused by many Southeast Asian Muslims could not be overly "extreme" or "radical" but tends to appear in a somewhat "negotiated" form.